Loss of pyruvate kinase M2 limits growth and triggers innate immune signaling in endothelial cells. Issue 1 (December 2018) - Stone, Oliver; El-Brolosy, Mohamed; Wilhelm, Kerstin; Liu, Xiaojing; Romão, Ana; Grillo, Elisabetta; Lai, Jason; Günther, Stefan; Jeratsch, Sylvia; Kuenne, Carsten; Lee, I-Ching; Braun, Thomas; et al.
Abstract Despite their inherent proximity to circulating oxygen and nutrients, endothelial cells (ECs) oxidize only a minor fraction of glucose in mitochondria, a metabolic specialization that is poorly understood. Here we show that the glycolytic enzyme pyruvate kinase M2 (PKM2) limits glucose oxidation, and maintains the growth and epigenetic state of ECs. We find that loss of PKM2 alters mitochondrial substrate utilization and impairs EC proliferation and migration in vivo. Mechanistically, we show that the NF-κB transcription factor RELB is responsive to PKM2 loss, limiting EC growth through the regulation of P53. Furthermore, S-adenosylmethionine synthesis is impaired in the absence of PKM2, resulting in DNA hypomethylation, de-repression of endogenous retroviral elements (ERVs) and activation of antiviral innate immune signalling. This work reveals the metabolic and functional consequences of glucose oxidation in the endothelium, highlights the importance of PKM2 for endothelial growth and links metabolic dysfunction with autoimmune activation in ECs. The glycolytic enzyme pyruvate kinase M2 (PKM2) is required for nucleotide synthesis and cell proliferation. Using gene expression and metabolomics analyses, the authors here show that PKM2 regulates methionine metabolism and DNA methylation in endothelial cells.